A new species of Noblella (Anura: Craugastoridae) from the Amazonian Slopes of the Ecuadorian Andes with Comments on Noblella lochites (Lynch) - Harvey, Michael B.; Almendáriz, Ana; M., Jorge Brito; R., Diego Batallas (Zootaxa, 2013)
We describe a new species of Noblella from wet, montane forest at the Sardinayacu Lake Complex between 1600–1920 m elevation in Morona Santiago, Ecuador. The new species differs from congeners in having three phalanges in the fourth finger, finely tuberculate skin on the dorsal body, pointed digital tips with marginal grooves on the fingers, a yellow to pale yellow venter, and a reduced facial mask not extending beyond the arm. The new species also lacks the pair of inguinal spots on the dorsal flanks of most congeners. Since its discovery in 1976, N. lochites has remained poorly known. We describe variation, color in life, and basic ecology of N. lochites based on a large series from the Cordillera del Condor.